The power of friends and neighbors: a review of community energy research - van der Schoor, Tineke; Scholtens, Bert (Current opinion in environmental sustainability, 2019)
•We investigate research on community energy.•Community energy is studied with highly different approaches.•There is little interaction between the approaches.•Research concentrates on a small number of ‘developed’ countries. The threat of climate change and the Paris agreement to limit global temperature rise to well below 2°C and to pursue efforts to limit it to 1.5°C has stimulated research on and broad commitment to community energy. We investigate this research. We assess how nine different approaches study community energy over time, which methods they use, which countries and regions they focus on, and where they discuss and publish. We analyze the keywords used to identify the research and investigate how these differ along the approaches. We show that community energy research took off only very recently and that especially ‘developed’ countries, in particular, the United Kingdom, United States, Germany, and the Netherlands, are studied. Different networks contribute to the understanding of community energy; however, the maturity and reach of these networks vary and there is limited exchange between research networks.